2019
DOI: 10.1016/j.dyepig.2018.10.025
|View full text |Cite
|
Sign up to set email alerts
|

A multifunctional tripodal fluorescent probe for the recognition of Cr3+, Al3+, Zn2+ and F− with controllable ESIPT processes

Abstract: Three 4- (benzo[d]thiazol-2-yl)-2,5-dihydroxybenzaldehyde fluorophores were introduced to construct a tripodal multifunctional ESPIT fluorescence probe L. The fluorescent analysis revealed that probe L exhibited excellent recognition capability towards Cr 3+ , Al 3+ , Zn 2+ and Fions with large Stokes shift. Furthermore, under the optimal conditions, the detection limit of probe L towards Cr 3+ , Al 3+ , Zn 2+ and Fwere low, of the order of 10 -8 M, which indicated that probe L was sensitive to these four ions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…This suggested that there were two kinds of emission sites in CDs 1 . Typical, ratiometric changes are considered to be the most accurate fluorescence detection method due to the self-calibration for environmental disturbance by two well-resolved wavelengths (Figure b (inset)). ,, However, UV–vis absorption spectra of CDs 1 under different pH conditions have been recorded (Figure S11). In contrast with the fluorescence spectra, no obvious changes were observed in the UV–vis absorption spectrum of the CDs as the pH increased from 1 to 14, which demonstrated that there was no ground-state complex formation.…”
Section: Resultsmentioning
confidence: 97%
“…This suggested that there were two kinds of emission sites in CDs 1 . Typical, ratiometric changes are considered to be the most accurate fluorescence detection method due to the self-calibration for environmental disturbance by two well-resolved wavelengths (Figure b (inset)). ,, However, UV–vis absorption spectra of CDs 1 under different pH conditions have been recorded (Figure S11). In contrast with the fluorescence spectra, no obvious changes were observed in the UV–vis absorption spectrum of the CDs as the pH increased from 1 to 14, which demonstrated that there was no ground-state complex formation.…”
Section: Resultsmentioning
confidence: 97%
“…Small organic fluorophores are indispensible tools for the construction of fluorescent probes because of the controllable optical properties such as bodipy, coumarin, rhodamine, fluorescein, etc . Among them, fluorophores derived from benzothiazole are widely used as the dye platform for designing of fluorescent probes . In our previous work, a ratiometric fluorescent probe HBT‐FA for sensing formaldehyde based on intramolecular charge transfer (ICT) mechanism by using aza‐cope reaction was constructed, which showed good ratio signals in aqueous and calf serums .…”
Section: Introductionmentioning
confidence: 99%
“…Generally, chemosensors with fluorescence enhancement are more efficient than fluorescence turn-off chemosensors [2429] because the paramagnetic nature of chromium(III) can cause fluorescence quenching of the fluorophore via the enhancement of spin–orbit coupling [3035]. So far, only a few successful examples of fluorescence enhancement sensors for Cr 3+ have been reported [3640]. Thus, developing new and effective fluorescence turn-on chemosensors for Cr 3+ is necessary.…”
Section: Introductionmentioning
confidence: 99%